The Efficacy of Citronella Extract (Cymbopogon nardus L.) in Inhibiting The Development of Anthracnose Disease in Chili Plants (Capsicum annuum L.) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2025)
Chili (Capsicum spp.) are members of the Solanaceae family, which includes many cultivated plants. They are frequently used by farmers and have a spicy taste that makes them a popular ingredient in Indonesian cuisine.The objective of this study is to observe the effect of citronella extract on the inhibition of anthracnose disease caused by Colletotrichum capsici in chili plants.This disease, caused by the aforementioned pathogen, manifests as blackish-brown patches on the affected area. The affected area undergoes desiccation and detachment over time.The experimental design employed a Group Randomized Design (GRD) method, comprising six treatments (P0, P1, P2, P3, P4, P5), each repeated five times.The experimental treatment involved the application of citronella extract, varying in dosage concentration among the treatments. This research was carried out on the Agrotech Training Center land of the Faculty of Agriculture, Sriwijaya University.